2008
DOI: 10.1182/blood-2008-04-149526
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell microvilli: a novel membrane structure associated with the multifocal synapse and T-cell clustering

Abstract: Polarizing effects of productive dendritic cell (DC)-T-cell interactions on DC cytoskeleton have been known in some detail, but the effects on DC membrane have been studied to a lesser extent. We found that T-cell incubation led to DC elongation and segregation of characteristic DC veils to the broader pole of the cell. On the opposite DC pole, we observed a novel membrane feature in the form of bundled microvilli. Each villus was approximately 100 nm in diameter and 600 to 1200 nm long. Microvilli exhibited h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 58 publications
6
57
0
Order By: Relevance
“…As the TCR clusters were observed before T-cell activation and were microvilli dependent, these results suggest that microvilli serve as the structural scaffold for clustering of TCRs and for the recruitment of microclusters upon TCR engagement. Moreover, these results are consistent with the observation of preformed TCR clusters in unactivated T cells (8,9) and mirror the selective localization of MHC molecules at the tips of membrane protrusions in APCs (11). This novel role of microvilli in positioning preformed TCR clusters has multiple implications regarding the spatial and dynamic regulation of T-cell activation.…”
supporting
confidence: 77%
“…As the TCR clusters were observed before T-cell activation and were microvilli dependent, these results suggest that microvilli serve as the structural scaffold for clustering of TCRs and for the recruitment of microclusters upon TCR engagement. Moreover, these results are consistent with the observation of preformed TCR clusters in unactivated T cells (8,9) and mirror the selective localization of MHC molecules at the tips of membrane protrusions in APCs (11). This novel role of microvilli in positioning preformed TCR clusters has multiple implications regarding the spatial and dynamic regulation of T-cell activation.…”
supporting
confidence: 77%
“…Interestingly, the role of the APC cytoskeleton in the modulation of microcluster dynamics and T-cell activation is reportedly absent in the most highly studied model for IS formation, namely the synaptic interactions between T-cells and antigen-presenting B-cells [10,[44][45][46]. Studies with B-lymphoma APCs have identified the rearrangement of surface receptors on the APC as a passive event and that B-cell cytoskeletal disruption does not modulate T-cell activation [47], however, studies are emerging on the importance of the APC cytoskeleton in IS formation, particularly in DC-mediated T-cell activation [37,42]. Here, the K562 aAPC, being of myeloid origin may share homologies with both DCs and osteoclast cells, also of myeloid lineage [48].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several EM studies reported well-maintained 3D structures of microvilli at T-cell-APC (26,27) or T-cell-T-cell interfaces (28) in vitro. Nevertheless, the presence of these structures in T cells migrating inside lymph nodes in search for antigen in vivo has been disputed (29)(30)(31)(32)(33).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our findings raise the intriguing possibility that, similar to L-selectin, whose localization on microvilli is critical for leukocyte capture by L-selectin ligands (6), enrichment of TCRs on these cellular projections may increase the probability of their encounter of antigens presented on counterprojections on APCs, primarily dendritic cells. Indeed, most APCs contain microvilli (26,48,49), and experiments suggested that MHC molecules, on which TCR antigenic ligands are presented, are enriched on these projections (49). Thus, molecules enriched on T-cell and APC microvilli may serve as firsthand participants in the T-cell activation process.…”
Section: Discussionmentioning
confidence: 99%